Albian ammonite faunas from Pech de Foix (Ariege, France) - Kennedy, W; Bilotte, M; Hansotte, M (1997)
New collections, and a review of surviving material in nineteenth century collections are the basis for a reappraisal of the age of the Albian succession around Pech de Foix (Ariege, France). 'Urgonien' limestones are overlain by a condensed phosphatic conglomerate with a fauna of the upper Lower Albian Douvilleiceras mammilatum Zone; the top of the underlying 'urgonien' can be no younger than lower Lower Albian. Resedimented olistoliths in the succeeding black marls overlie uncondensed Mammilatum Zone sediments, and are in turn overlain by marls with autochthonous lower Middle Albian, Hoplites dentatus Zone, Hoplites spathi Subzone faunas. The higher parts of the black marls yield faunas of the lower Upper Albian Hysteroceras varicosum Subzone and possibly the H. orbignyi Subzone of the Mortoniceras inflatum Zone. This sedimentary sequence records two major events; the first, tethyan extension, corresponds to the Lower Albian eustatic rise in sea-level; the second, of regional extent is associated with the breakup of 'urgonian' carbonate platforms in response to the opening and transtension of the Albian basins of the Pyrenees. The Albian sequence of Pech de Foix dates this latter event to within the lower Middle Albian. The new, precise dating of the sequence leads to a revision of the timing of sedimentological, palaeogeographic and structural events in the north Pyrenees during the Albian.